Interfaces naturais e o reconhecimento das línguas de sinais - Silva, Renato Kimura da (2013)
Interface is an intermediate layer between two faces. In the computational context, we could say that the interface exists on the interactive intermediation between two subjects, or between subject and program. Over the years, the interfaces have evolved constantly: from the monochromatic text lines to the mouse with the exploratory concept of graphic interfaces to the more recent natural interfaces ubique and that aims the interactive transparency. In the new interfaces, through the use of body, the user can interact with the computer. Today is not necessary to learn the interface, or the use of these interfaces is more intuitive, with recognition of voice, face and gesture. This technology advance fits well to basic needs from the individuals, like communication. With the evolution of the devices and the interfaces, is more feasible conceive new technologies that benefits people in different spheres. The contribution of this work lays on understanding the technical scenario that allow thinking and conceiving natural interfaces for the signal recognition of Sign Languages and considerable part of its grammar. To do so, this research was guided primarily in the study of the development of computer interfaces and their close relationship with videogames, basing on the contributions of authors such as Pierre Lévy, Sherry Turkle, Janet Murray and Louise Poissant. Thereafter, we approach to authors as William Stokoe, Scott Liddell, Ray Birdwhistell, Lucia Santaella and Winfried Nöth, concerning general and specific themes spanning the multidisciplinarity of Sign Languages. Finally, a research was made of State of Art of Natural Interfaces focused on the recognition of Sign Languages, besides the remarkable research study related to the topic, presenting possible future paths to be followed by new lines of multidisciplinary research